Anatomic changes after hyoid suspension for obstructive sleep apnea: an MRI study - Stuck, Boris; Neff, Wolfgang; Hörmann, Karl; Verse, Thomas; Bran, Gregor M.; Baisch, Alexander; Düber, Christoph; Maurer, Joachim T. (Otolaryngology - head and neck surgery, 2005)
OBJECTIVE: To assess the effects of isolated hyoid suspension on subjective and objective parameters of obstructive sleep apnea and to evaluate changes in upper airway anatomy with the help of standardized magnetic resonance imaging., STUDY DESIGN AND SETTING: Fifteen patients received isolated hyoid suspension. Changes in respiratory disturbance index were assessed with polysomnography, and anatomical changes with standardized magnetic resonance imaging. Snoring, daytime sleepiness, and functional parameters were assessed with questionnaires. Lateral x-ray cephalometry was performed preoperatively., RESULTS: Mean respiratory disturbance index was reduced from 35.2 ± 19.1 to 27.4 ± 26.2. Forty percent of the patients were classified as responders. Daytime sleepiness improved significantly. Relevant changes in upper airway anatomy could not be detected. There were no remarkable differences between responders and nonresponders in regard to imaging., CONCLUSIONS: Hyoid suspension is effective only in a subgroup of patients and does not lead to relevant changes in airway diameters in the awake patient. Magnetic resonance imaging and x-ray cephalometry do not add additional information for patient selection., SIGNIFICANCE: The reported clinical effects of hyoid suspension are more likely due to functional changes in airway collapsibility than to an enlargement of the upper airway.